2014
DOI: 10.1371/journal.pone.0101803
|View full text |Cite
|
Sign up to set email alerts
|

Getting “Just Deserts” or Seeing the “Silver Lining”: The Relation between Judgments of Immanent and Ultimate Justice

Abstract: People can perceive misfortunes as caused by previous bad deeds (immanent justice reasoning) or resulting in ultimate compensation (ultimate justice reasoning). Across two studies, we investigated the relation between these types of justice reasoning and identified the processes (perceptions of deservingness) that underlie them for both others (Study 1) and the self (Study 2). Study 1 demonstrated that observers engaged in more ultimate (vs. immanent) justice reasoning for a “good” victim and greater immanent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 45 publications
(68 reference statements)
2
26
0
Order By: Relevance
“…Our findings from Study 1 conceptually replicated previous UJR research (e.g. Harvey & Callan, 2014a) in that participants engaged with greater UJR when exposed to a victim who had suffered greatly, versus minimally, and perceptions of deserving ultimate justice mediated this relationship. In other words, a high suffering victim poses a greater threat to participants' BJW than a victim who is not suffering, presumably due to such suffering being unfair and undeserved.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our findings from Study 1 conceptually replicated previous UJR research (e.g. Harvey & Callan, 2014a) in that participants engaged with greater UJR when exposed to a victim who had suffered greatly, versus minimally, and perceptions of deserving ultimate justice mediated this relationship. In other words, a high suffering victim poses a greater threat to participants' BJW than a victim who is not suffering, presumably due to such suffering being unfair and undeserved.…”
Section: Discussionsupporting
confidence: 84%
“…Alternatively, research within the BJW literature provides evidence for other individual difference measures that influence the extent of UJR, such as religiosity (Harvey & Callan, 2014b) and self-esteem (Harvey & Callan, 2014a). Firstly, Harvey and Callan (2014b) found that people who self-report as highly religious, are more likely to believe a victim will have a later fulfilling and meaningful life, regardless of whether the victim was a bad (i.e.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The relative neglect of intragroup and intergroup mechanisms in this literature is all the more striking because different theoretical approaches—that are frequently cited by researchers working on morality—emphasize that moral principles are considered so important because they indicate shared notions about “right” and “wrong” that regulate the behavior of individuals. Indeed, prominent approaches to morality commonly acknowledge that general moral principles such as the “golden rule” can be interpreted differently in different contexts or by groups of people who translate these into specific behavioral guidelines (e.g., Churchland, 2011; Giner-Sorolla, 2012; Greene, 2013; Haidt & Graham, 2007; Haidt & Kesebir, 2010; Harvey & Callan, 2014). This is also the key message of the seminal study on moral reasoning by Haidt et al (1993).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Results from animal studies (e.g., de Waal, 1996) or insights into universal justice principles (e.g., Greenberg & Cropanzano, 2001) do not necessarily help us to address moral behavior in modern societies. This also requires the reconciliation of people who endorse different political orientations (Haidt & Graham, 2007) or adhere to different religions (Harvey & Callan, 2014). The observation that “good people can do bad things” further suggests that we should look beyond the causes of individual deviance or delinquency to understand moral behavior.…”
mentioning
confidence: 99%
“…From this perspective, reasoning that a random bad outcome was caused by someone’s prior immoral actions allows people to maintain the belief that things happen for a reason, and the reason can be found in the target’s prior misdeeds—people get what they deserve. Evidence for this account comes from research documenting that perceived deservingness underpins people’s immanent justice attributions (e.g., Harvey & Callan, 2014) and immanent justice reasoning increases when the importance of a just-world to people is heightened (e.g., Callan, Harvey, Dawtry, & Sutton, 2013).…”
mentioning
confidence: 99%